Redox Responses in Patients with Sepsis: High Correlation of Thioredoxin-1 and Macrophage Migration Inhibitory Factor Plasma Levels. (5th August 2010) - Brenner, Thorsten; Rosenhagen, Claudia; Steppan, Jochen; Lichtenstern, Christoph; Weitz, Jürgen; Bruckner, Thomas; Martin, Eike O.; Hoffmann, Ursula; Weigand, Markus A.; Hofer, Stefan
Abstract : Background . Redox active substances (e.g., Thioredoxin-1, Macrophage Migration Inhibitory Factor) seem to be central hubs in the septic inflammatory process. Materials and Methods . Blood samples from patients with severe sepsis or septic shock (n = 15 ) were collected at the time of sepsis diagnosis ( t 0), and 24 ( t 24) and 48 ( t 48) hours later; samples from healthy volunteers (n = 18 ) were collected once; samples from postoperative patients (n = 28 ) were taken one time immediately after surgery. In all patients, we measured plasma levels of IL-6, TRX1 and MIF. Results . The plasma levels of MIF and TRX1 were significantly elevated in patients with severe sepsis or septic shock. Furthermore, TRX1 and MIF plasma levels showed a strong correlation ( t 0: r sp = 0.720, ρ = 0.698 / t24 : r sp = 0.771, ρ = 0.949 ). Conclusions . Proinflammatory/~oxidative and anti-inflammatory/~oxidative agents show a high correlation in order to maintain a redox homeostasis and to avoid the harmful effects of an excessive inflammatory/oxidative response.